Biodiversity and biogeographic affinity of benthic amphipods from the Yucatan Shelf: an analysis across the warm Northwest Atlantic ecoregions. Issue 8 (17th November 2021) - Paz-Ríos, Carlos E.; Pech, Daniel; Carrera-Parra, Luis F.; Simões, Nuno
Abstract : The biodiversity and biogeographic affinity of benthic amphipods from the Yucatan continental shelf with the warm Northwest Atlantic ecoregions were analysed using species occurrence data from benthic marine habitats of the continental shelf (< 200 m). A comprehensive collection of distributional data (presence-only) was obtained from different sources and newly-sampled material and sorted according to 12 ecoregions from the Northwest Atlantic. Distribution of species richness, taxonomic distinctness, endemism, and spatial replacement was analysed across ecoregions. The faunal relationships among ecoregions were explored using a clustering analysis based on the Sørensen dissimilarity index, and a cladistic analysis of distributions and endemism based on parsimony. Results from the Yucatan shelf showed a representative species pool from the highly diverse Northwest Atlantic amphipod fauna (202 spp.), with intermediate levels of endemism and taxonomic distinctness. Results from dissimilarity and parsimony showed two groups of amphipod assemblages consistent with two of the main biogeographic provinces in the Northwest Atlantic: Carolinian and Caribbean. The incorporation of the Yucatan shelf species assemblage, as an ecoregion into the used classification scheme, had implications on the amphipods biogeographic affinity identification. The Yucatan ecoregion led to a latitudinal spatial replacement of amphipod species across ecoregions and provinces, revealing that the Yucatan ecoregion has a higher biogeographic affinity with tropical ecoregions of the Caribbean province. The spatial replacement of amphipods suggests that the Southern Gulf of Mexico ecoregion has a higher affinity with warm-temperate ecoregions of the Carolinian province and is proposed as a transitional zone between the identified provinces.